Investigation of the co-identification of hexogen and pentrite as particles and co-adsorbed on copper oxide nanoparticles by using nanocalorimetry. Issue 40 (30th August 2016) - Bonnot, K.; Schlur, L.; Spitzer, D.
Abstract : When both RDX and PETN are present in air, their competition for detection can be determined by fast heating nanocalorimetry. Abstract : Fast-heating calorimetry experiments have been performed on a hexogen and pentrite particle mixture and on the same explosives adsorbed on CuO nanoparticles. Low heating rates allow the identification of both explosive particles. However, once adsorbed, their identification depends on their concentration ratio. An excess of PETN prevents the RDX identification.